E-book dan pengguna perpustakaan perguruan tinggi di Jakarta - Yusnimar Yusnimar (Al Maktabah, 2014)
Electronic book is one of the product development of information and communication technology, which is now easily accessible over the internet. This situation means that the access to books is not limited and can be done by all people. Anyone can access books and publish a book on the internet. It means that people now have the ability of an informed (information leterate). University’s library is an institution which is much influenced by the ability of an informed, because it acts as a development capacity center of its informed. This is where librarians are expected to manage the availability knowledge in a variety of resources. In other words, e -books are available in a variety of multi- media internet. Interaction between Internet users grow from how to publish theirself, their minds and their works using multi-media. The presence of e -book role in this research is understood as a paradigm of thinking to revitalize the way librarians interact and serve the users. E-book is a change centered to the users. Therefore, the model library services must undergo a change that oriented to service desired physical and virtual users (users oriented).